Immune checkpoint inhibitors and myocarditis in advanced non-small cell lung cancer: a nationwide cohort study - Fu-Xiao Li; Jia-Xin Cai; Ji-Bin Li; Kong-Jia Luo; Shi-Yu Wang; Wei-Hua Meng; Feng Sha; Zhi-Rong Yang; Allan Hackshaw; Jin-Ling Tang (Cardio-Oncology)
Abstract Objective Evidence suggests immune checkpoint inhibitor (ICI) can increase the risk of myocarditis. We investigated it in a large national cohort in China. Methods Patients with stage IIIB-IV non-small cell lung cancer (NSCLC) using data from China's National Anti-Tumor Drug Surveillance System between January 2013 and December 2021. Exposure density sampling was applied to control for immortal time bias. Multivariate Cox regression with time-dependent exposures was used to examine the association between ICI therapy and the incidence of myocarditis while controlling for confounders. Results 55,219 patients were included. The median age was 61 years, and 62% were males. At one-year follow-up (median 335 days), there were 26 cases of myocarditis among ICI users and 28 cases among ICI non-users (a cumulative incidence of 4.8 and 0.6 per 1000 person-years respectively). The adjusted hazard ratio (HR) of myocarditis for ICI users was 7.41 (95% confidence interval [CI]: 3.29–16.67). For programmed cell death protein 1 inhibitor users the HR was 8.39 (95% CI: 3.56–19.77). No significant interactions were observed in subgroup analysis. The results remained unchanged in sensitivity analyses. Conclusions This study showed that ICI therapy considerably increased the risk of myocarditis, supporting the need for closer monitoring of patients receiving ICI therapies.